2015
DOI: 10.1007/s10517-015-2849-1
|View full text |Cite
|
Sign up to set email alerts
|

Low Doses of Hyperbaric Oxygenation Effectively Decrease the Size of Necrotic Zone in Rats with Experimental Myocardial Infarction

Abstract: We studied the effect of a single session of hyperbaric oxygenation on the size of risk, ischemic, and necrotic zones in rat myocardium after irreversible occlusion of the coronary artery and excessive oxygen pressure of 0.02 and 0.1 MPa. Myocardium infarction was reproduced by ligation of the left coronary artery. The size of the risk, ischemic, and necrotic zones was planimetrically evaluated. Hyperbaric oxygenation (60-min session) was performed 3 h after artery occlusion at excessive oxygen pressure of 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The field of therapeutic IH is dominated by the use of HBO, and HBO therapy is approved by the FDA to treat 15 indications 24. Additionally, although not FDA approved for these indications, studies appear to suggest that HBO therapy may ameliorate other conditions including myocardial infarction,25 hip fractures,2627282930 stroke,331323334353637 peri-surgical healing,3839404142 and traumatic brain injury 33543444546…”
Section: Discussionmentioning
confidence: 99%
“…The field of therapeutic IH is dominated by the use of HBO, and HBO therapy is approved by the FDA to treat 15 indications 24. Additionally, although not FDA approved for these indications, studies appear to suggest that HBO therapy may ameliorate other conditions including myocardial infarction,25 hip fractures,2627282930 stroke,331323334353637 peri-surgical healing,3839404142 and traumatic brain injury 33543444546…”
Section: Discussionmentioning
confidence: 99%
“…Hyperbaric oxygenation (HBO 2 ) is commonly used to improve injuries related to hypoxia and ischemia, including infections, such as meningococcal sepsis and gaseous gangrene [ 1 , 2 ], myocardial infarction [ 3 ], cerebral ischemia [ 4 ], and even some neurodegenerative disorders [ 5 7 ]. Experimental [ 8 ] and clinical data suggest that intermittent HBO 2 [ 9 ] decreases tissue edema, increases nitric oxide (NO) synthesis, changes vascular reactivity to stimuli [ 10 ], and inhibits neuroinflammatory factors' expression and apoptotic pathways [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 HBO was shown to induce cardioprotection through anti-apoptotic effect and decreased infarct size in a rat model of MI. 5,6 Several small clinical trials also demonstrated the beneficial effect of HBO in patients with acute coronary syndrome by reducing the infarct size, and the risk of major cardiovascular events and death. 7 Exosomes are 40-90 nm-sized extracellular vesicles of endosomal origin that play a crucial role in intercellular processes.…”
mentioning
confidence: 99%